Experimenting different Jawi spelling conditions to gauge their cognitive complexity - Khazriyati Salehuddin,; Winskel, Heather (Penerbit UKM, 2015)
Although traditionally, Malay was predominantly written in the Arabic script (Jawi), the Roman script has become the standard script for the Malay language after the Second World War due to the relative complexity of Jawi in comparison to the Roman script. One factor that makes reading Jawi a cognitively complex process is the complex and confusing use of vowel letters in the spelling of Malay words in Jawi; hence, making the Jawi spelling system appear to be rather inconsistent. Currently, the vowel phonemes in Malay words in Jawi are represented differently in different syllables either using vowel letters or not represented at all. Two reading experiments on Malay bi-syllabic words written in Jawi were conducted with two groups of readers. In Experiment 1, 28 Malay native speakers and 13 Arabic native speakers read 200 Malay bi-syllabic words in Jawi as quickly and as accurately as possible to investigate the naming latencies of words written in Jawi with and without diacritics. In Experiment 2, 30 Malay 13- and 14-year-olds read 108 Malay bi-syllabic words in Jawi to investigate if adding vowel diacritics and/or vowel letters to represent Malay vowels facilitates reading Jawi. Both experiments were conducted using DMDX, a Win 32-based display system for psychological experiments that records reaction times to visual and auditory stimuli. Results are presented in terms of the subjects‟ reading accuracy (correct responses) and latency (reaction times). To a great extent, adding vowel diacritics to the Jawi spelling system does facilitate reading. This study also shows that two forms of permutations in the Jawi spelling system can help make reading Jawi a cognitively less complex process for readers.